Genomic Sequences of Epizootic Hemorrhagic Disease Viruses Isolated from Florida White-Tailed Deer - Subramaniam, Kuttichantran (Genome Announc, 2017)
Epizootic hemorrhagic disease virus (EHDV) serotypes 1 and 2 were isolated from Florida white-tailed deer in 2015 and 2016, respectively, and their genomes were completely sequenced. To our knowledge, these are the first full genome sequences for EHDV-1 and -2 from Florida.